Retaining an age-diverse workforce through HRM: the mediation of work engagement and affective commitment - Sousa, I. C.; Ramos, S.; Carvalho, H. (German Journal of Human Resource Management: Zeitschrift für Personalforschung, 2021)
An aging population and an increasingly age-diverse workforce exemplify the complex challenge that age represents for most managers today. For that reason, research has shown the importance of designing and implementing human resources (HR) practices that meet age-related differences in workers’ motives and needs. Drawing on signaling and social exchange theories, the current study investigated a first stage moderated parallel multiple mediation model. We examined the mediating roles of work engagement and affective commitment in the relationship between age-diversity practices and turnover intention, as well as the moderating role of work centrality in these mediated relationships. Using a sample of 802 Portuguese workers, the study supported the parallel multiple mediation hypotheses. Further, the findings revealed that work centrality moderated the relationship between age-diversity practices and turnover intention via work engagement, but not via affective commitment. Age-diversity practices may motivate those workers who place less importance on work to be more engaged, which, in turn, reduces their intentions to leave the organization. Moreover, all workers, regardless of the importance that work plays in their life, are more emotionally attached to the organization and more willing to stay when there are age-diversity practices. Thus, to retain a healthy and productive age-diverse workforce, organizations should implement age-diversity practices. Empirical and practical implications are discussed.